Cochrane Database of Systematic Reviews 2010
DOI: 10.1002/14651858.cd008367
|View full text |Cite
|
Sign up to set email alerts
|

Oral hygiene care for critically ill patients to prevent ventilator associated pneumonia

Abstract: To assess the effect of oral hygiene care on ventilator associated pneumonia (VAP) in critically ill patients receiving mechanical ventilation in hospital settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
33

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(96 citation statements)
references
References 45 publications
2
61
0
33
Order By: Relevance
“…Similarly, in critically ill ventilated patients, oral hygiene with chlorhexidine mouthwash has been shown to reduce rates of VAP, and has been included as a component of a successfully evaluated 'VAP care bundle'. 7,10 Chlorhexidine mouthwash would be an inexpensive measure for use in the immediate pre-and postoperative period for surgical patients. Oral care (chlorhexidine mouthwash or mechanical cleaning) was shown to be associated with a reduced relative risk of pneumonia in a metaanalysis incorporating non-ventilated hospital inpatients and nursing home residents (though there was a high risk of bias in included studies).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in critically ill ventilated patients, oral hygiene with chlorhexidine mouthwash has been shown to reduce rates of VAP, and has been included as a component of a successfully evaluated 'VAP care bundle'. 7,10 Chlorhexidine mouthwash would be an inexpensive measure for use in the immediate pre-and postoperative period for surgical patients. Oral care (chlorhexidine mouthwash or mechanical cleaning) was shown to be associated with a reduced relative risk of pneumonia in a metaanalysis incorporating non-ventilated hospital inpatients and nursing home residents (though there was a high risk of bias in included studies).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of previous studies exploring the effectiveness of tooth brushing, chlorhexidine and swabbing with cold water, the researchers designed the intervention protocol for the present study.…”
Section: Methodsmentioning
confidence: 99%
“…According to a recent meta‐analysis of 17 randomized controlled trials, oral care with chlorhexidine significantly reduced the prevalence of ventilator‐associated pneumonia (VAP) . Another systematic review reported moderate quality evidence from 17 randomized controlled trials that chlorhexidine mouth rinse or gel was associated with a reduction in VAP when used as part of the oral hygiene care routine, compared to a placebo or usual care, but there was insufficient evidence that it improved oral health . Tooth brushing is an effective method of oral care to reduce dental plaque and bacteria as well as to decrease the risk of lower respiratory tract infection and VAP .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, research has shown a significant correlation between oral bacteria and VAP (Heo et al , ), indicating that an oral health care program plays a very important role in VAP prevention (Shi et al , ; Berry et al , ). Moreover, the current ventilator bundle care, in general, is a multidisciplinary (e.g.…”
Section: Introductionmentioning
confidence: 99%